BATIK MOTIFS FOR CHILDREN CASUAL FASHION INSPIRED BY BEDOUIN TRIBE HOUSE - Lisa Tri Agustin; Arif Jati Purnomo (Runtas: Jurnal Fesyen dan Wastra Nusantara, 2024)
The fashion-artwork entitled Batik Motifs for Children Casual Fashion Inspired by Bedouin Tribe House is as a form of effort to introduce culture and traditions to children. The purpose of creation is to apply the traditional Bedouin house batik motifs for casual clothing for girls aged 10 years old. The methods of creating the fashion pieces are exploration stage, design stage, and creation stage. The process of creating works starts from the exploration stage, which was searching data about traditional Bedouin houses. Making batik motif designs that are embodied in children's casual clothing is applied to create the piece of art using batik tulis technique which were dab-cover-dip coloring using remasol, naptol and indigosol dyes using Japanese cotton and primissima. The color selection brings out cheerful colors. Starting from the design process, scratching, cutting, coloring, melorod, sewing, to making accessories. Casual clothing is clothing that is simple, practical, and comfortable to wear for children's daily playing activities. This work created 4 pieces of batik motifs, they are: Imah Sawarna, Imah Ngahiji, Imah Salonjor, Imah Kahuripan. With that created 4 fashion pieces: Inleum, Makaul, Galis, Bageur. All of the fashion pieces mentioned above were equipped with accessories to support the whole look.